HAK ASASI MANUSIA BIDANG EKONOMI SOSIAL DAN BUDAYA MENURUT PERUBAHAN UUD 1945 - SUBAWA, I MADE (Kertha Patrika, 2012)
Human right is elementary rights which naturally attach at human it self, having the character as universal andhave to judicial protect. Therefore cannot lessen, to be hijacked and for this reason have to be defended.In Indonesia in Chapter of XA the changed of constitution 1945 determined about human right. But its bearingwith rights in economic section, social and culture, identify have not yet detail and clear. Because of rights relatedto rights in economic area, social and culture, still spread over the changed of constitution 1945.Impact to rights of economic, social and culture, happened when state fail to fulfill such basic rights wich meant.In this case individual or citizens have the right to claim accomplishment to rights of economic, social and culture,through advocatie.
Keywords: Rights Basic of economic, social and culture, appreciative to fulfill, impact, advocatie